Detecting RNA-protein proximity at DNA double-strand breaks using combined fluorescence in situ hybridization with proximity ligation assay - Alagia, A; Ketley, RF; Gullerova, M (Cell Press, 2023)
RNA transcribed at DNA double-strand breaks (DSBs) contributes to accurate DNA repair. Here, using the repair factors 53BP1 and TIRR as examples, we combine the fluorescence in situ hybridization (FISH) and proximity ligation assay (PLA) techniques to determine protein proximity to DSB-transcribed RNA. In this FISH-PLA protocol, we detail steps for designing DNA probes and image analysis using CellProfiler™ software. This approach has many potential applications for the study of the RNA-binding proteins and nascent RNA interactions. For complete details on the use and execution of this protocol, please refer to Ketley et al. (2022).1